ANTIBIOFILM ACTIVITY OF LACTOBACILLUS RHAMNOSUS GG AND SACCHAROMYCES BOULARDII METABOLITES IN RELATION TO POLYRESISTANT GRAM-NEGATIVE MICROORGANISMS - Isaуenko, O.Yu.; Knysh, O.V.; Ryzhkova, T.M.; Kotsar, O.V.; Dyukareva, G.I. (World of Medicine and Biology, 2020)
In order to avoid the chronic forms of diseases development and to effectively treat patients with acute manifestations of infections it is necessary not only to fight pathogenic microorganisms with antibacterial drugs, but also to learn how to influence the pathogens biofilm formation. In this work, the study of the antibiofilm activity of the original metabolites of Lactobacillus rhamnosus GG and Saccharomyces boulardii, obtained by cultivating probiotics in disintegrated microorganisms, was carried out. The antibiofilm effect of probiotic substances concerning strains polyresistant to antibacterial drugs (Pseudomonas aeruginosa PR, Klebsiella pneumoniae PR, Lelliottia amnigena (Enterobacter amnigens) PR) is dependent on the activity of L. rhamnosus GG and S. boulardii filtrates and on the individual sensitivity of the pathogens test culture. Statistically significant reduction of the biofilms formation by pathogens’ microbial cells occurred with the use of metabolites of bacteria and of fungi (р
Keywords: biofilms; products of lactobacilli and saccharomyces metabolism; gram-negative microorganisms polyresistant to antibacterial drugs